PKM-Perancangan Automatic Temperatur Control Menggunakan Pd Pada Mesin Pengering Gabah Tipe Rotary - Imaduddin, Ilmrrizki; Prasetya, Faisal Wiji; Hasan, Muhammad Hasan Basri; Sofyan, Fachrudin; Jalaluddin; Rizki, Farhan; Afin, M (Universitas Sulawesi Barat, 2023)
During the Community Service (PKM) activities carried out by students and lecturers in Opo-opo Village, Krejengan District, Probolinggo Regency, to assist farmers in the grain drying process. Where the simple drying process generally takes 3 days. To overcome the problem of manual drying, the PKM will design an automatic temperature control using pd on a rotary type grain drying machine. The test results were carried out 3 times, including the first test with 8 kg of grain with a fire setting, a temperature of 57 ℃ was obtained, and the required drying time was 50 minutes, so that the final weight was obtained lower than the initial weight due to a decrease in water content with the result the final grain weight was 7.23 kg and there was a decrease in grain weight of 1.37 kg. For the two grain tests of 7 kg with the fire setting, a temperature of 57 ℃ was obtained, and the drying time required was 30 minutes, so that the final weight was obtained which was lower than the initial weight due to a decrease in water content with the final grain weight being 6.73 kg and there was a decrease in grain weight of 1.87 kg. And for the three grains of 6.15 kg with the fire setting, a temperature of 69 ℃ was obtained, and the required drying time was 20 minutes, so that the final weight was obtained which was lower than the initial weight due to a decrease in water content with the final grain weight being 6. 40 Kg and there was a decrease in grain weight of 1.75 Kg.